PERSONALITY TRAITS OF PAULINE IN "EVERYTHING, EVERYTHING" NOVEL - Galuh Fitriana Sakti (ReALL - Research on Applied Linguistics and Literature, 2022)
Personality has been described as being an individual's characteristic pattern of thinking, feeling and acting across a wide range of situations. It affects how we make decisions, solve problems, handle conflict and cope with stress. This research aims to investigate the character, Pauline Furukawa Whittier, in the novel â€œEverything Everythingâ€ by Nicola Yoon. Pauline is a loving mother but was blinded by the trauma that she got from losing her husband and son. This affects her action in treating her only daughter, Maddy. In analyzing personality traits, The Big Five Personality from McRae & Costa (1992) is used. The researcher also employed a qualitative research method in collecting the data. The result revealed that Pauline is described as a woman who has neuroticism and conscientiousness. These two personalities are dominant due to Paulineâ€™s traumatic experience that made her really need to be so protective to look after her daughter even by manipulating her own daughter.